CSS Pocket Reference, Fourth Edition Visual Presentation for the Web - Meyer, Eric A. (O'Reilly Media, 2011)
When you're working with CSS and need a quick answer, CSS Pocket Reference delivers. This handy, concise book provides all of the essential information you need to implement CSS on the fly. Ideal for intermediate to advanced web designers and developers, the 4th edition is revised and updated for CSS3, the latest version of the Cascading Style Sheet specification. Along with a complete alphabetical reference to CSS3 selectors and properties, you'll also find a short introduction to the key concepts of CSS.